A General Attraction Model and Sales-Based Linear Program for Network Revenue Management Under Customer Choice - Gallego, Guillermo; Ratliff, Richard; Shebalov, Sergey (Operations Research, 2015)
This paper addresses two concerns with the state of the art in network revenue management with dependent demands. The first concern is that the basic attraction model (BAM), of which the multinomial logit (MNL) model is a special case, tends to overestimate demand recapture in practice. The second concern is that the choice-based deterministic linear program, currently in use to derive heuristics for the stochastic network revenue management problem, has an exponential number of variables. We introduce a generalized attraction model (GAM) that allows for partial demand dependencies ranging from the BAM to the independent demand model (IDM). We also provide an axiomatic justification for the GAM and a method to estimate its parameters. As a choice model, the GAM is of practical interest because of its flexibility to adjust product-specific recapture. Our second contribution is a new formulation called the sales-based linear program (SBLP) that works for the GAM. This formulation avoids the exponential number of variables in the earlier choice-based network RM (revenue management) approaches and is essentially the same size as the well-known LP formulation for the IDM. The SBLP should be of interest to revenue managers because it makes choice-based network RM problems tractable to solve. In addition, the SBLP formulation yields new insights into the assortment problem that arises when capacities are infinite. Together these contributions move forward the state of the art for network revenue management under customer choice and competition.